On Floating Conclusions - Schuster, Daniela; Broersen, Jan; Prakken, Henry (College Publications, 2023)
When there are two lines of argument that contradict each other but still end up with the same conclusion, this conclusion is called a floating conclusion. It is an open topic in skeptical defeasible reasoning if floating conclusions ought to be accepted. Interestingly, the answer seems to be changing for different examples. In this paper, we propose a solution for explaining the different treatments of the floating conclusion in the various examples from the literature. We collect the examples from the literature, extend them with additional examples and test various hypotheses for explaining the difference by means of the examples. We will argue for a framework that accepts a floating conclusion by default but allows for reasons to deviate from the default in order to reject it. These reasons nicely explain the different underlying patterns of our intuitions.